Evidence for ammonium conductance in a mouse thick ascending limb cell line - Lee, Soojung (Physiol Rep, 2017)
In this study, we examined an ammonium conductance in the mouse thick ascending limb cell line ST‐1. Whole cell patch clamp was performed to measure currents evoked by NH (4)Cl in the presence of BaCl(2), tetraethylammonium, and BAPTA. Application of 20 mmol/L NH (4)Cl induced an inward current (−272 ± 79 pA, n = 9). In current‐voltage (I–V) relationships, NH (4)Cl application caused the I–V curve to shift down in an inward direction. The difference in current before and after NH (4)Cl application, which corresponds to the current evoked by NH (4)Cl, was progressively larger at more negative potentials. The reversal potential for NH(4)Cl was +15 mV, higher than the equilibrium potential for chloride, indicating that the current should be due to NH (4) (+). We then injected ST‐1 poly(A) RNA into Xenopus oocytes and performed two‐electrode voltage clamp. NH (4)Cl application in the presence of BaCl(2) caused the I–V curve to be steeper. The NH (4) (+) current was retained at pH 6.4, where endogenous oocyte current was abolished. The NH (4) (+) current was unaffected by 10 μmol/L amiloride but abolished after incubation in Na(+)‐free media. These results demonstrate that the renal cell line ST‐1 produces an NH (4) (+) conductance.